Kedudukan dan Fungsi Singir Sebagai Sastra Jawa Pesisir Kajian Genre dan Sosiologi - Moh Muzakka Mussaif (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Singir as Javanese poetry is not less noticed by literary experts. These poems were not recorded in various catalogs of manuscripts, not recorded in the periodization of Javanese literature, and only a few experts examined them. Even though the population and tradition of singir still exist and develop until now. This paper tries to position the singir as a type of coastal literature while looking at its social functions. To uncover this problem, genre and sociology studies are needed. The results of genre studies show that the structure of singir is different from other types of Javanese literature, even different from Malay poetry. As for the sociology study, it was found that the singir had the functions of entertainment, education and teaching, and spiritual functions